Role of adipokinetic hormone in stimulation of salivary gland activities: the fire bug Pyrrhocoris apterus L. (Heteroptera) as a model species - Vinokurov, Konstantin; Bednářová, Andrea; Tomčala, Aleš; Stašková, Tereza; Krishnan, Natraj; Kodrík, Dalibor (Journal of insect physiology, 2014)
The effect of adipokinetic hormone (Pyrap-AKH) in stimulating the function of insect salivary glands (SGs) in extra-oral digestive processes was studied in the firebug, Pyrrhocoris apterus L. (Heteroptera). The analyses were performed on samples of SGs and extracts of linden seeds, a natural source of the bug's food. The SGs from 3-day old P. apterus females (when the food ingestion culminates), primarily contained polygalacturonase (PG) enzyme activity, whereas the level of lipase, peptidase, amylase and α-glucosidase was negligible. The transcription of PG mRNA and enzymatic activity were significantly increased in SGs after Pyrap-AKH treatment. The piercing and sucking of linden seeds by the bugs stimulated the intrinsic enzymatic cocktail of seeds (lipase, peptidase, amylase, glucosidase), and moreover the activity of these enzymes was significantly enhanced when the seeds were fed on by the Pyrap-AKH treated bugs. Similarly, a significant increase in PG activity was recorded in linden seeds fed on by hormonally-treated bugs or when injected by SG extract from hormonally treated ones as compared to untreated controls. The mechanism of AKH action in SGs is unknown, but likely involves cAMP (and excludes cGMP) as a second messenger, since the content of this compound doubled in SGs after Pyrap-AKH treatment. This new and as yet undescribed function of AKH in SGs is compared with the effect of this hormone on digestive processes in the midgut elucidated earlier.
Keywords: AKH; hmyzí hormony; Polygalacturonase; Salivary glands; Pyrrolidonecarboxylic Acid; Oligopeptides; AMP cyklický; oligopeptidy; Salivary Glands; modely u zvířat; cAMP; Cyclic AMP; trávení; Cyclic GMP; Digestion; ženské pohlaví; guanosinmonofosfát cyklický; zvířata; kyselina pyrrolidonkarboxylová; Digestive enzymes; slinné žlázy; Heteroptera; Insect Hormones; Female; Models, Animal; Animals